Barcelona - Abella, Soledad (Carlton: Lonely Planet, 2022)
Lonely Planet's Experience Barcelona is your guide to unforgettable experiences and local surprises. Wonder at La Sagrada Familia, dine on tapas and paella, and get ready to enjoy one of Europe's most famed nightlife scenes - all guided by local experts with fresh perspectives. Uncover Barcelona's best experiences and get away from the everyday!
Includes index.
Keywords: Barcelona (Spain) -- Guidebooks; Description and Travel